The Multi-item Bisection Auction - Albin Erlanson (Lund University, School of Economics and Management, Department of Economics, 2011)
This paper proposes an iterative sealed-bid auction for selling multiple heterogeneous items with unit-demand agents. It generalizes the single item bisection auction (Grigorieva Et. al, 2007) to the environment with multiple heterogeneous items. We show that it elicits a minimal amount of information on preferences required to find the Vickrey-Clark-Groves outcome (Clarke, 1971, Groves, 1973, Vickrey, 1961), when there are two items for sale and an arbitrary number of agents.
Keywords: C72; D44; 330; Bisection Auction; Multi-item; Unit-demand; Sealed-bid